MECHANISMS OF PLANT ADAPTATION TO PHOSPHORUS - Dilnoza Masobirova (American Journals Publishing, 2023)
Phosphorus is one of the seventeen essential nutrients required for plant growth. Despite its importance, it is limiting crop yield on more than 40% of the world's arable land. Moreover, global P reserves are being depleted at a higher rate and according to some estimates, there will be no soil P reserve by the year 2050. This is a potential threat to sustainable crop production. Most of the P applied in the form of fertilizers may be adsorbed by the soil and is not available for plants lacking specific adaptations.
Keywords: adaptation mechanism, nutrient stress, phosphorus efficiency, soil phosphorus management.